MONITORING KEBIJAKAN PENGGUNAAN PLASTIK DI KOTA SEMARANG - Riyana Afila; Kismartini Kismartini; R Slamet Santoso (Journal of Public Policy and Management Review, 2022)
The amount of plastic waste in Semarang City which has continued to increase over 3 years is the background for Govevernment of Semarang City to issue Semarang Mayor’s Regulation 27 of 2019 concerning about Controlling of plastic use in Semarang City. However, the implementation of this policy, not all policy targets have been implemented. This is because the government is not firm in monitoring, so the policy targets tend to be easy. This is the background of this research. This study aims to analyze the monitoring function of plastic use policy in Semarang City and find out the driving factors and the obstacle factors. The method of this research is descriptive qualitative with data collection techniques by way of interviews, observations, and documentations. This study uses the theory of monitoring functions according to William Dunn (1981), namely compliance, auditing, accounting, and explanation. The results of this research are the monitoring that carried out by Dinas Lingkungan Hidup Kota Semarang has been going well. However, the monitoring activities carried out have not reached all policy targets. According to four functions monitoring by William Dunn, the compliance function is still not fulfilled yet. This is because there is no Standart Operating Procedure that regulated and the officers has not implement it in accordance with the regulation, especially in the terms of sanctions enforcement. The driving factors in monitoring of this policy are the communication of polict implementers and policy targets. Meanwhile, the obstacle factors are policy standards and resources